Bile acids in immunity: Bidirectional mediators between the host and the microbiota - Godlewska, Urszula; Bulanda, Edyta; Wypych, Tomasz P. (Frontiers in Immunology, 2022)
Host-microbiota interactions are bidirectional. On one hand, ecological pressures exerted by the host shape the composition and function of the microbiota. On the other, resident microbes trigger multiple pathways that influence the immunity of the host. Bile acids participate in both parts of this interplay. As host-derived compounds, they display bacteriostatic properties and affect the survival and growth of the members of the microbial community. As microbiota-modified metabolites, they further influence the microbiota composition and, in parallel, modulate the immunity of the host. Here, we provide a comprehensive overview of the mechanisms behind this unique dialogue and discuss how we can harness bile acids to treat intestinal inflammation.